From the Feeling of Passing into Understanding the Meaning of Eternity - Mirzoyan, Valeri (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
The feeling of ephemerality makes a person look for the meaning of life. The article discusses the role of philosophy and philosophizes for understanding the meaning relating to contemporary life issues. In particular, it is stressed that if a person «forgets» these issues in household problems, if he or she is not satisfied with the answers that give religions, arts, wealth, power, then philosophy might help him or her understand his or her personal responsibility for his life, as well as for the maintenance of intelligent life on planet Earth.
Keywords: ephemerality, meaning of life, fear of death, Sisyphus job, the end of the world, philosophy, humankind, David Invincible